Biomass and abundance of sesarminae crabs in a high shore Malaysian Mangrove Forest - Leh, Charles M.U; A, Sasekumar; Chew, L.L. (Malaysian Journal of Science, 2010)
The biomass and abundance of grapsid crabs and other macrobenthos in the disturbed and undisturbed upper shore mangroves of the Kapar Mangrove Forest. Reserve, Kiang, Malaysia were studied. Nine species of the Sesarminae crabs which occurred in the disturbed forest contributed a biomass of 5.61 +1.67 g dry wt m-2 out of the total macrofaunal biomass of 9.83 g dry wt m-2. In contrast, only 5 species of Sesarminae occurred in the undisturbed forest with a biomass of 8.25+ 2.1 g dry wt m-2 out of a total macrofaunal biomass of 18.72 g dry wt m-2. Perisaesarma onychophorum (de Man) occurred with the highest biomass (2.66 +0.93 g dry wt m-2) in the disturbed forest while P. eumople (de Man) occurred with the highest biomass in the undisturbed forest (6.03 +1.53g dry m-2). Forest structure and sediment water content in the high shore influences colonization by the Sesarminae crabs, while timber harvests create an impact on the macrobenthic community.